حماية المدنيين في زمن الحروب الاهلية بين الشريعة الاسلامية والقانون الدولي سوريا انموذجا - Abdul Salam Milad Al mabruk
The international community has made great efforts in developing and writing the law of human rights, including international humanitarian law. It is line with the Geneva Conventions to ensure the protection of civilians and non- combatants during the battle of serious violations of human rights and punish perpetrators of human rights in cases of international conflict and civil wars. The issues focused on the lack of implementation mechanism which requires the protection of civilians under international humanitarian law and the inability of the international community to punish war criminals from member states in the Security Council of the United Nations (UN) because they have the power of veto. The study aims to explain the concept of protection of civilians during the civil war in accordance with Islamic Law as well as explaining the reasons for the outbreak of civil war and human rights abuses. The study also identified a gap in international law which does not give protection to human rights during in the civil war with the interest of the great powers to protect civilians in the civil war. This study takes an inductive approach, analysing the facts, historical events and battles according to Islamic Sharia and international law. The study found that international humanitarian law is completely paralyzed due to the control of the member states of the Security Council against international decision-making process that moves away from the basic principles of fairness and failed to provide adequate protection for human rights during the war. This study suggests a mechanism reform decision-making in the Security Council and expand the powers of the UN tribunal in punishing war criminals and to address gaps in international law which does not give protection to human rights during the civil war.